PEMBELAJARAN LITERASI DI LPTK UNDANA MENYONGSONG GENERASI EMAS INDONESIA - Nai, Firmina A. (Jurnal Lazuardi, 2024)
Schelfhout et al. (2006) quoted by Mehrak (in Asean EFL Journal, p. 3) via www.asean-efl-journal.com>pta_oct_08 , said that: to produce good prospective teachers, LPTK needs to equip prospective teachers with "(1 ) master the content knowledge of the discipline they are specialized to teach; (2) have skills and knowledge about teaching/learning in order to teach properly; (3) work in school contexts; (4) notice any short comings in their teaching and constantly try to improve it; (5) take on a broader pedagogical and moral responsibility”. With the key words master, skills, work, notice, and take, the statement above is directly related to learning and learning designs that can help bridge the quality of teacher education at LPTK and the needs of schools as stakeholders. This research accommodates ethnographic studies from the perspective of James P. Spradley (1980) who describes the culture of a group including three aspects, namely cultural behavior (what is done), cultural knowledge (what is known), and cultural artifacts (what is used) (in Muhyidin, 2023) The results of an ethnographic study of cultural knowledge and cultural artifacts of initial reading and writing learning at SDN Maulafa, Kupang City in 2023, show that there is a gap that is too wide between the pragmatic provisions of teachers and the results of theoretical studies at LPTK. The results of the research show that the majority of lower grade teachers carry out initial reading and writing lessons using the spelling method, letter card method, and alphabet method. This proves a very significant difference between the learning materials at LPTK and the learning content that prospective teachers will apply in the workplace. If early reading and writing learning models are used by teachers, then the issue of literacy as one of the young generation's vehicles for the golden era will not be achieved.